Open Data for Sustainable Development - Petrov, Oleg; Gurin, Joel; Manley, Laura (World Bank, Washington, DC, 2016)
The “open data” principle is becoming an increasingly important part of the data revolution, which is recognized worldwide as a key engine for achieving the post-2015 UN Sustainable Development Goals. Open data—publicly available online information that can be used for any purpose at little or no cost—represent one of the most underutilized key assets of modern government. Open data initiatives are often directed at converting open data into formats that can be reused for private sector development, jobs creation, economic growth, and more effective governance and citizen engagement. A 2013 study estimated that using open data in seven sectors of economic activity could create $3 trillion to $5 trillion annually in economic value worldwide. The direct, annual economic value of public governmental data has been estimated at up to €40 billion for the European Union and £2 billion for the United Kingdom. Numerous examples illustrate how the use of open data can give significant support to achieving the post-2015 UN Sustainable Development Goals.